2018
DOI: 10.1039/c7an02106b
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic analysis of the molecular composition of oral cavity squamous cell carcinoma and healthy tongue tissue

Abstract: A Raman tissue spectrum is a quantitative representation of the overall molecular composition of that tissue. Raman spectra are often used as tissue fingerprints without further interpretation of the specific information that they contain about the tissue's molecular composition. In this study, we analyzed the differences in molecular composition between oral cavity squamous cell carcinoma (OCSCC) and healthy tissue structures in tongue, based on their Raman spectra. A total of 1087 histopathologically annotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Raman spectroscopy is a nondestructive and label-free optical technique, and has demonstrated great clinical merits for tumor margin assessment in numerous types of cancer, including skin [6], brain [7,8], oral cavity [9,10], breast [11,12], and stomach [13]. Those studies either use fiber-optical Raman probe for single point sampling or Raman microscopy (also called Raman microspectroscopy) for optical imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is a nondestructive and label-free optical technique, and has demonstrated great clinical merits for tumor margin assessment in numerous types of cancer, including skin [6], brain [7,8], oral cavity [9,10], breast [11,12], and stomach [13]. Those studies either use fiber-optical Raman probe for single point sampling or Raman microscopy (also called Raman microspectroscopy) for optical imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy (1-error rate) is the proportion of correct predictions, including correct positive and negative predications based on the selected samples [42]. The low specificity of the tongue indicates miss-classification between healthy tissue sublayers (surface squamous epithelium, muscle, and gland) and the OSCC structure, which has been discussed in an earlier study [43] and the section on validation methods.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since the oral tissue is heterogeneous, it comprises of different structures and layers. Cals [43] reported that the sub-layers of a healthy tissue structure (surface squamous epithelium, muscle) have the same protein, lipids, and nucleic acid as OSCC or tumor tissues of the tongue. Therefore, the miss-classification between healthy tissues sublayers (surface squamous epithelium, muscle, and gland) and the OSCC structures was greater than other sub-sites.…”
Section: Validation Methodsmentioning
confidence: 99%
“…Previously, CRM has been successful in the spatial resolution of biomedical environments like tissue samples or bacterial cells [14][15][16][17][18]. However, the acquired signals from these biomedical components are highly complex [19][20][21].…”
Section: Introductionmentioning
confidence: 99%